Extensive brainstem infiltration, not mass effect, is a common feature of end-stage cerebral glioblastomas. Issue 4 (10th November 2019) - Drumm, Michael R; Dixit, Karan S; Grimm, Sean; Kumthekar, Priya; Lukas, Rimas V; Raizer, Jeffrey J; Stupp, Roger; Chheda, Milan G; Kam, Kwok-Ling; McCord, Matthew; Sachdev, Sean; Kruser, Timothy; et al.
Abstract: Background: Progress in extending the survival of glioblastoma (GBM) patients has been slow. A better understanding of why patient survival remains poor is critical to developing new strategies. Postmortem studies on GBM can shed light on why patients are dying. Methods: The brains of 33 GBM patients were autopsied and examined for gross and microscopic abnormalities. Clinical-pathologic correlations were accomplished through detailed chart reviews. Data were compared with older published autopsy GBM studies that predated newer treatment strategies, such as more extensive surgical resection and adjuvant temozolomide. Results: In older GBM autopsy series, mass effect was observed in 72% of brains, with herniation in 50% of all cases. Infiltration of tumor into the brainstem was noted in only 21% of those older cases. In the current series, only 10 of 33 (30%) GBMs showed mass effect ( P = 0.0003), and only 1 (3%) showed herniation ( P < 0.0001). However, extensive GBM infiltration of the brainstem was present in 22 cases (67%, P < 0.0001), with accompanying destruction of the pons and white matter tracts. There was a direct correlation between longer median patient survival and the presence of brainstem infiltration (16.1 mo in brainstem-invaded cases vs 9.0 mo in cases lacking extensive brainstem involvement; P = 0.0003). Conclusions: With improving care, severe mass effect appears to be less common in GBM patients today, whereas dissemination, including life-threatening brainstem invasion, is now more pronounced. This has major implications regarding preclinical GBM models, as well as the design of clinical trials aimed at further improving patient survival.